2002
DOI: 10.1136/jme.28.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting physicians' decisions to forgo life-sustaining treatments in terminal care

Abstract: Objectives: Treatment decisions in ethically complex situations are known to depend on a physician's personal characteristics and medical experience. We sought to study variability in decisions to withdraw or withhold specific life-supporting treatments in terminal care and to evaluate the association between decisions and such background factors.Design: Readiness to withdraw or withhold treatment options was studied using a terminal cancer patient scenario with alternatives. Physicians were asked about their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
1
6

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(95 citation statements)
references
References 23 publications
8
80
1
6
Order By: Relevance
“…Physician characteristics, such as age, gender, experience, or education, explain variation in decisions in end-of-life care [16], and these characteristics could also explain some variation in cooperation found in our study. Furthermore, we were unable to measure outcomes, hence we could not analyse any possible relation between quality of care and GP cooperation with other caregivers.…”
Section: Discussionmentioning
confidence: 58%
“…Physician characteristics, such as age, gender, experience, or education, explain variation in decisions in end-of-life care [16], and these characteristics could also explain some variation in cooperation found in our study. Furthermore, we were unable to measure outcomes, hence we could not analyse any possible relation between quality of care and GP cooperation with other caregivers.…”
Section: Discussionmentioning
confidence: 58%
“…The majority of physicians in this survey chose both to withhold tube feeding and to withdraw tube feeding after 3 months without improvement.The confounding influences of patient and family wishes have been noted in previous studies [5][6][7]10,15,24 and physicians often override the advance directives of patients. 7,14 Even patients recognize that their families may not agree with their advance directives, and some prefer for their families' wishes to supersede their own.…”
Section: Discussionmentioning
confidence: 94%
“…Physicians' end of life treatment preferences have been associated with physician ethnicity, religion, age, and personality style, [5][6][7][8][9][10][11][12][13] while other studies have found associations between treatment decisions and patient or institutional factors. 10,14,15 Physician ethnicity was associated with tube feeding decisions, 16 and patient and institutional factors associated with tube feeding in nursing home patients have been identified in previous observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…O estudo de McLean et al 25 constatou que a terapêutica mais freqüentemente retirada foi o suporte ventilatório sendo mantidas a sedação e a analgesia. Na Finlândia, Hinkla et al 26 observaram os fatores que afetam os médicos quanto às decisões de recusa ou suspensão de tratamentos em vítimas de doença cancerosa em fase final e constataram que os tratamentos mais recusados foram a transfusão sangüínea e a profilaxia da trombose. Moritz et al 27 , em um estudo que avaliou a atitude dos médicos intensivistas brasileiros diante da RST, mostraram que a sedação e a analgesia foram as intervenções menos recusadas ou suspensas e que os métodos dialíticos constituíram a terapêutica mais comumente recusada ou suspensa.…”
Section: Introductionunclassified